2010
DOI: 10.1111/j.1600-051x.2010.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of whole-body vibration time on peri-implant bone healing: a histomorphometrical animal study

Abstract: time of loading significantly influenced the effect of the WBV on peri-implant bone healing. Twice 1.25 min. of loading appears to have the most favourable effect. LMHF loading with a particular time sequence can stimulate peri-implant bone healing and formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…Since the process of osseointegration of oral implants involves the bone healing process, it was assumed that HF loading might positively affect peri-implant bone healing and osseointegration. Ogawa and co-workers have confirmed a bone anabolic response of HF loading, even when applied indirectly, on the peri-implant tissue mineralization in noncompromised rat bone [24]. This was discernible during the implant osseointegration cascade at tissue level already after 7 days of healing.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Since the process of osseointegration of oral implants involves the bone healing process, it was assumed that HF loading might positively affect peri-implant bone healing and osseointegration. Ogawa and co-workers have confirmed a bone anabolic response of HF loading, even when applied indirectly, on the peri-implant tissue mineralization in noncompromised rat bone [24]. This was discernible during the implant osseointegration cascade at tissue level already after 7 days of healing.…”
Section: Discussionmentioning
confidence: 72%
“…WBV experiments have evidenced the advantageous effects of HF loading on bone [16][17][18] and on titanium implant osseointegration [23]. Ogawa and co-workers recently reported, by means of rat animal experiments and quantitative histology, that HF loading via WBV can promote peri-implant bone healing and enhance implant osseointegration [23,24]. However, the latter-referred experiments did not make use of an impaired bone model.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggested that in the presence of loading, osseointegration can occur early (Branemark et al, 1999) with greater deposition of mineralized tissue around the implant (Ogawa et al, 2011). This phenomenon suggests that functional stimulation could alter the osseointegration process through the release of molecules that act as modulators of osteogenesis and osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, WBV seems to be superior to the localized loading. WBV has been found to extensively influence periimplant bone remodelling and hence led to significant increases of BIC and BF [17,18,35]. Compared with Load frequency affects implant healing X. Zhang et al 1701 the control, more than 10 per cent extra BIC was found in case of WBV after four weeks.…”
mentioning
confidence: 99%